Informal firms in developing countries entrepreneurial stepping stone or consolation prize? - John Bennett (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
We analyse potential dynamic benefits for a firm from having the option of adopting informal status. Informality may be a stepping stone, without which formality might never be achieved. This result obtains for a broad range of realistic parameter values, suggesting a potential dynamic case for government support of informal firms. Informality may alternatively play a converse role as a consolation prize, a firm only entering an industry (formally) because it recognizes that if profitability is disappointing, it can switch to informality. However, this result obtains for a range of parameter values so narrow to be of no practical significance.
Keywords: O17; M21; D2; 330; informality; entrepreneurship; Informeller Sektor; Entwicklungsländer